Postoperative Physician Phone Calls as a Method to Decrease Urgent Care and Emergency Department Returns After Ambulatory General Surgery. Issue 10 (25th October 2020) - Massoumi, Roxanne L.; Crain, Nikhil; Zhu, Catherine; Moore, Alexandra; Oland, Gabriel; Ghukasyan, Razmik; Lu, Yang; Ye, Linda; Hadaya, Joseph; Dacey, Michael; Schumm, Max; Oh, Nicholas; et al.
Unplanned returns after ambulatory surgery pose a burden to patients and health care providers alike. We hypothesized that a postoperative phone call by a physician would decrease avoidable returns to urgent care (UC) or the emergency department (ED) in the week after anorectal (AR), laparoscopic cholecystectomy (LC), inguinal hernia repair (IHR), and umbilical hernia repair (UHR) operations. A retrospective analysis from 1/2011 to 12/2015 across 14 Kaiser hospitals was conducted to determine baseline UC/ED return rates of patients pre-call. Between 10/2017 and 06/2019, physicians placed phone calls to patients within postoperative days (PODs) 1-4. The cohorts were compared using chi-squared analysis with significance determined at P < .05. In total, 276 patients received a call, with the majority placed on PODs 1-3. There were no statistically significant differences in return rates between the pre- and post-call groups. All of the AR, 50.0% of LC, 66.7% of IHR, and 50.0% of UHR patients returned prior to phone call placement. Our data indicate that a physician phone call does not help in decreasing UC/ED returns. However, it is noteworthy that many of the returns occurred pre-call placement. Future directions should be aimed at placing earlier postoperative phone calls.